Encyclopedia of earthquakes and volcanoes - Gates, Alexander E., 1957-; Ritchie, David, 1952 Sept. 18- (New York : Checkmark Books, 2007)
Provides information on earthquakes and volcanic eruptions in various regions of the world, major quakes and eruptions throughout history, and geologic and scientific terms.
Preface : an essay on plate tectonics -- Acknowledgments -- Introduction -- Entries A-Z -- Appendix A. Chronology of earthquakes and volcanic eruptions -- Appendix B. Eyewitness accounts of major eruptions and quakes -- Appendix C. Further reading and Web sites -- Appendix D. The deadliest earthquakes -- Appendix E. The deadliest volcanoes -- Appendix F. The highest magnitude earthquakes -- Appendix G. The frequency of occurrence of earthquakes -- Appendix H. Magnitude v. ground motion and energy.
Ritchie's name appears first on the previous ed.
Includes bibliographical references (p. 313-315) and index.
Keywords: Earthquakes -- Encyclopedias; Volcanoes -- Encyclopedias